Implementasi Model Pembelajaran “Blended Learning” dalam Peningkatan Motivasi Belajar Peserta Didik - Ratnasari, Tria (FONDATIA, 2023)
This research is a qualitative field research, where the aim is to analyze the implementation of the blended learning model in increasing the learning motivation of students in elementary schools and madrasah ibtidaiyah as well as supporting and inhibiting factors that affect the implementation of the learning model. The method used is the method of observation, interviews and documentation. Where samples are drawn randomly. Based on the results of the research, it shows that the implementation of the blended learning model in increasing the learning motivation of students in elementary schools and madrasah ibtidaiyah is carried out in three stages, namely learning design, material creation and material delivery. These three stages are of course applied inseparably from the media and methods used by the school and madrasah in accordance with the conditions. As for the supporting and inhibiting factors that affect the implementation of the learning model, it is seen by using a SWOT analysis at each stage. Where the supporting factors are indicated by the advantages and opportunities, and the inhibiting factors are indicated by the shortcomings and threats faced when the implementation of the learning model runs.